CFD Analysis on the Effect of Vortex Generator on Sedan Car using ANSYS Software - Ismail, Muhammad Pirdaus; Ishak, Izuan Amin; Samiran, Nor Afzanizam; Mohammad, Ahmad Faiz; Mohd Salleh, Zuliazura; Darlis, Nofrizalidris (International Journal of Integrated Engineering, 2022)
Nowadays, the demand for a high-speed car increases in which vehicle stability and fuel economy are the primary concern. The vehicle's aerodynamics plays a crucial role as it influences the overall performance of the vehicles. In the exploration of car aerodynamics, it involves studying various forces that act on a car while moving on the road, i.e., drag force, lift force. The leading causes of aerodynamic drag for automotive vehicles are the flow separation at the vehicles' rear end. By reducing the drag force, it is possible to increase the fuel economy. The research is focused on the effect of a vortex generator (VG) on a sedan car aerodynamics. The objective is to simulate fluid flow analysis for a sedan car that uses VG and without VG, to assess the effect of a different configuration of VG and the impact of a varying number of VG mounted on a sedan car in terms of flow pattern development and coefficient of drag (Cd). This study is conducted using two identical sedan car models, i.e., with VG and without VG. The flow around the vehicle has been considered incompressible. It is obtained by solving the incompressible form of the Reynolds Navier-Stokes (RANS) equations combined with the k-Îµ turbulence model. The simulation is run for different configuration of VG that acquire different radius of fillet, i.e., VG-1 (5 mm), VG-2 (30 mm) and VG-3 (50 mm) and for different number of VG that is mounted on a sedan car, i.e., 0 VG, 1 VG, 3 VG, 5 VG, 7 VG, and 9 VG. The data and results taken from this simulation show that the smallest fillet radius of VG, i.e., VG-1 (5 mm), is the best VG to be used on a sedan car. The results also show that, as the number of VG's increases, the drag coefficient is decreased. Hence, the best number of VG's to be used on a sedan car are nine VG's.